PENGARUH LITERASI KEUANGAN, PENDAPATAN, DAN KONTROL DIRI TERHADAP PERILAKU KEUANGAN MAHASISWA YANG SUDAH BEKERJA - Yehuda Shaharoni; Colline, Fredella (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STIE Pontianak, 2023)
This study aims to determine the effect of financial literacy, income, and self-control on the financial behavior of working students. The research method used is a quantitative method with primary data collection techniques using a questionnaire method via Google form which is distributed to 97 active students who are working in companies and have income. The research using Multiple Regression Analysis with SPSS tool to analyze the data. Of the 97 students who have worked, the results show that financial literacy has a significant positive effect on financial behavior, while income and self-control have no effect on financial behavior.